Universal insurance in health in Peru: an approximation to 10 years of its implementation.: Aseguramiento universal en salud en el Perú: una aproximación a 10 años de su implementación - Jumpa-Armas, David Victorino (2019)
The policy of the Universal Health Insurance (AUS) established that access to health services will be carried out through the financial intermediation of health insurance, establishing for this four axes of "reform": plan of benefits, financing and payments, targeting of subsidies, service provision and regulation. The policy of the AUS was based on the theory of quasi-markets where the intention of the State is to avoid being the provider of resources and the service provider at the same time; instead, it seeks to become the primary provider of funds to a variety of private, public and nonprofit providers, all operating in competition against each other.